Carotid artery atherosclerosis, MRI-defined structural brain abnormalities, and cognitive performance in elderly American Indians: The Strong Heart Study - Ali, Tauqeer; Buchwald, Dedra; Shibata, Dean; Roman, Mary J.; Verney, Steven; Howard, Barbara V.; Umans, Jason; Cole, Shelley; West, Cynthia; Zhang, Ying; Reese, Jessica; Rhoades, Dorothy A.; et al. (Frontiers in Epidemiology, 2025)
Background and objectiveAmerican Indian populations face disproportionately high rates of atherosclerotic cardiovascular disease (CVD), yet the potential consequences of mid-life carotid atherosclerosis on brain health and cognition later in life remain poorly understood. This study addresses a critical knowledge gap by evaluating whether subclinical carotid atherosclerosis in midlife is associated with later-life structural brain abnormalities and cognitive performance in a large cohort of American Indian adults from the Strong Heart Study. This is the first investigation to explore these associations in this underserved and understudied population, using longitudinal data with vascular, neuroimaging, and cognitive measures.MethodsA total of 783 participants (mean age 59.9 years) underwent carotid ultrasonography between 1998 and 1999 to assess intima-media thickness and plaque. Between 2010 and 2013, participants received brain magnetic resonance imaging to assess infarcts, hemorrhages, white matter lesions, and brain atrophy. Cognitive function was also evaluated during this period. Multivariable regression models adjusted for sociodemographic, behavioral, and clinical CVD risk factors were used to assess associations.ResultsGreater intima-media thickness was associated with more severe sulcal widening, and presence and extent of plaque were associated with poorer verbal fluency; both findings remained significant after adjustment for sociodemographic, behavioral, and clinical risk factors. No significant associations were observed between carotid measures and the presence of infarcts, hemorrhages, or white matter lesions.ConclusionThese findings suggest that subclinical carotid atherosclerosis in midlife may contribute to later-life brain atrophy and cognitive vulnerability, particularly in verbal fluency, among American Indians.